CORRELATION BETWEEN HEARING LOSS AND COGNITIVE IMPAIRMENT IN THE ELDERLY: CORRELACIÓN ENTRE PÉRDIDA AUDITIVA Y DETERIORO COGNITIVO EN EL ADULTO MAYOR. - Cordero Pinedo, Félix (2024)
ABSTRACT Introduction: Hearing loss or hearing loss in the elderly is generally caused by degenerative changes typical of aging and can influence the cognitive deterioration of the person, which is manifested by different changes in memory as age increases. Objective: To determine the relationship between hearing loss and cognitive impairment in the elderly. Method: Descriptive, correlational and cross-sectional study. Otoscopy, audiometry and the Pfeiffer questionnaire were performed in 104 adults over 65 years of age, who attended the Otorhinolaryngology service of the Arzobispo Loayza National Hospital. The otoscope, the audiometer and the Pfeiffer questionnaire were used as instruments. Analyzing the relationship using Spearman's Rho correlation coefficient. Results: Hearing loss was found in 58 cases (55.8%) and normal hearing in 46 cases (44.2%). When applying the Pfeiffer questionnaire to determine cognitive status, an average global score of 8.5 was obtained, determining that values ​​less than 8 are considered mild cognitive impairment. Evidencing mild cognitive impairment in 7% of normoacusics and in 26% of hypoacusics. When performing Spearman's Rho correlation, a high positive correlation was found between hearing loss and cognitive impairment (0.864), significant (0.000<0.05). Conclusions: There is a high positive relationship between hearing loss and cognitive impairment in the elderly. Keywords: Hearing loss, hearing loss, presbycusis, cognitive impairment.